1982
DOI: 10.2307/2425291
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Differences Between an Old and a New Colony of Black-tailed Prairie Dogs (Cynomys ludovicianus)

Abstract: Two colonies of black-tailed prairie dogs (Cynomys ludovicianus) in Wind Cave National Park, South Dakota, were compared during 1979 and 1980 to investigate the effects of (1) the age of the population and (2) the availability of resources on specific demographic parameters. The younger colony was surrounded by, and expanding into, unused available habitat. The older colony had little available habitat for expansion. At the younger colony (1) there was a greater proportion of successful pregnancies; (2) the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 12 publications
1
42
1
Order By: Relevance
“…While little is known about the landscape-scale dynamics of black-tailed prairie dog colonies prior to European settlement, studies conducted outside the current distribution of plague indicate that colonies can remain in the same approximate location for several decades to several centuries (Garrett et al 1982;Knowles and Knowles 1994;Carlson and White 1987). Locations of colony boundaries may be constrained by topography and soil types (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While little is known about the landscape-scale dynamics of black-tailed prairie dog colonies prior to European settlement, studies conducted outside the current distribution of plague indicate that colonies can remain in the same approximate location for several decades to several centuries (Garrett et al 1982;Knowles and Knowles 1994;Carlson and White 1987). Locations of colony boundaries may be constrained by topography and soil types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Collins and Barber (1985) described prairie dog disturbance as continuous, but did not specify a time frame. Some studies suggest prairie dogs may have a natural impetus to relocate due to changes in vegetative characteristics that develop over multiple decades of prairie dog occupancy (Garrett and Franklin 1988;Cincotta 1985;Garrett, et al 1982), but little is known about the landscape-scale dynamics of colonies prior to European settlement of central North America. This lack of information may be due in part to the wide range of anthropogenic factors which have dramatically affected prairie dog colonies since European settlement (Miller and Cully 2001;Lomolino and Smith 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age ratios did not change after plague, antibody development was higher among adults; all but one adult showed antibodies to Y. pestis, whereas only one juvenile developed antibodies. Because juveniles do not immigrate (Garrett and Franklin, 1988), most juveniles must have avoided plague by occupying uninfected regions of the colony. Cully et al (1997) found similar effects of plague in the Gunnison's prairie dog; colonies were extirpated or reduced by 99%, and roughly half of the survivors developed antibodies to Y. pestis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, following the population crash, intraspecific competition for forage should have decreased, providing the few survivors better access to food, resulting in improved body condition. Whatever the underlying mechanism, colonies supporting large healthy individuals should grow more quickly because large prairie dogs reach sexual maturity at a younger age, produce larger litters, and exhibit better over-winter survival (Garrett et al, 1982;Rayor, 1985b). The role of healthy survivors should not be discounted in colony recovery.…”
Section: Discussionmentioning
confidence: 99%